2019
DOI: 10.1111/acem.13672
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Double Sequential Defibrillation: A Matched Case–Control Study

Abstract: Objectives: The goal of our study was to determine whether prehospital double sequential defibrillation (DSD) is associated with improved survival to hospital admission in the setting of refractory ventricular fibrillation/pulseless ventricular tachycardia (VF/pVT).Methods: This project is a matched case-control study derived from prospectively collected quality assurance/ quality improvement data obtained from the San Antonio Fire Department out-of-hospital cardiac arrest (OHCA) database between January 2013 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…The details are shown in the forest plot (Figure 2E). The Begg's Test resulted in P = 0.296 > 0.05, implying that there is no publication bias in the three studies (18,19,21). Double sequential external defibrillation (DSED) was not superior to standard defibrillation in terms of survival to good neurological outcomes in patients with RVF, and there was no significant difference between the two in good neurological recovery outcomes.…”
Section: Good Neurologic Outcome (Cpc 1∼2)mentioning
confidence: 90%
See 1 more Smart Citation
“…The details are shown in the forest plot (Figure 2E). The Begg's Test resulted in P = 0.296 > 0.05, implying that there is no publication bias in the three studies (18,19,21). Double sequential external defibrillation (DSED) was not superior to standard defibrillation in terms of survival to good neurological outcomes in patients with RVF, and there was no significant difference between the two in good neurological recovery outcomes.…”
Section: Good Neurologic Outcome (Cpc 1∼2)mentioning
confidence: 90%
“…The six studies (4,8,14,17,19,21) were tested for heterogeneity (I 2 = 46.9% < 50%), and P = 0.094 < 0.1 of the Q-test, suggesting that the heterogeneity among the article selected for this study was statistically significant, and further examining L' Abbe Plot (Figure 2F) and Radial Plot (Figure 3B), The analysis of the study showed no difference between DSED and standard defibrillation in the return of spontaneous circulation.…”
Section: Return Of Spontaneous Circulationmentioning
confidence: 99%
“…For the critical outcome of good neurological survival at hospital discharge we identified verylow-certainty evidence (down-graded for risk of bias and imprecision) from five observational studies. 17À21 19 (Fig. 2).…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…For the critical outcomes of survival with favourable neurological outcome 29 , 30 , 31 and survival to hospital discharge 29 , 30 , 31 , 32 , 33 , 34 and the important outcomes of survival to hospital admission, 29 , 30 , 32 , 33 ROSC, 29 , 30 , 31 , 32 , 33 , 34 , 35 and termination of VF, 31 , 34 , 35 we identified only observational studies. The overall certainty of evidence was rated as very low for all outcomes, primarily because of a very serious risk of bias.…”
Section: Defibrillation Strategies For Ventricular Fibrillation or Pumentioning
confidence: 99%